2018
DOI: 10.1002/tht3.267
|View full text |Cite
|
Sign up to set email alerts
|

The Cut-Free Approach and the Admissibility-Curry

Abstract: The perhaps most important criticism of the nontransitive approach to semantic paradoxes is that it cannot truthfully express exactly which metarules preserve validity. I argue that this criticism overlooks that the admissibility of metarules cannot be expressed in any logic that allows us to formulate validity-Curry sentences and that is formulated in a classical metalanguage. Hence, the criticism applies to all approaches that do their metatheory in classical logic. If we do the metatheory of nontransitive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…that a metainference is represented as valid in T just in case that metainference is valid for T . Hlobil (2018) has shown that the obvious way of parsing that principle trivialises any theory defined with a classical meta-theory. Inspired by recent research on metainferences such as Barrio et al (2015), Barrio et al (2020) and Dicher and Paoli (2019), this paper proposes and develops an approach according to which the requirement for metainferences should be restricted from (globally) valid metainferences to locally valid metainferences; that a metainference is represented as valid in T if and only if the metainference is locally valid for T .…”
Section: Logical Disagreement and Comparing Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…that a metainference is represented as valid in T just in case that metainference is valid for T . Hlobil (2018) has shown that the obvious way of parsing that principle trivialises any theory defined with a classical meta-theory. Inspired by recent research on metainferences such as Barrio et al (2015), Barrio et al (2020) and Dicher and Paoli (2019), this paper proposes and develops an approach according to which the requirement for metainferences should be restricted from (globally) valid metainferences to locally valid metainferences; that a metainference is represented as valid in T if and only if the metainference is locally valid for T .…”
Section: Logical Disagreement and Comparing Alternativesmentioning
confidence: 99%
“…A first stab at a requirement for representing metainferences is presented in the following form by Hlobil (2018) but the idea of a requirement along these lines is also suggested by Barrio et al (2016) and Rosenblatt (2017): 13 if X 0 T Y 0 and . .…”
Section: Validity Proof (Vp): Ifmentioning
confidence: 99%
“….. , we note that . 10 is of the form for some , and so, as before, we construct a maximal such that for all finite :…”
Section: Theorem 38mentioning
confidence: 99%
“…By "valid," I really mean here "derivable". For, as Hlobil argues in[10], a validity predicate cannot capture the admissible rules on pain of going non-classical in the metalanguage 14. This definition serves as an alternative to the explicit definition of validity in terms of truth preservation.…”
mentioning
confidence: 99%
“…Recently, Barrio, Rosenblatt, and Tajer (2015) and Barrio, Pailos, and Szmuc (2018) draw attention to certain paraconsistent aspects of ST (and consequently, of CFOLE). Both papers have shown thatthrough some suitable translation-the set of valid inferences in LP coincides with the set of valid meta-inferences in ST. First among these this objection has been criticized by Hlobil (2018 and2019). In these papers Hlobil argues that (i) the criticism applies to all approaches that do their metatheory in classical logic and (ii) asking a logic to express its own admissible metarules may not be a good idea.…”
Section: A Misleading View About What a Logic Ismentioning
confidence: 99%